A New Research on Da Yuan Ben Cao - Guang SHI; Jin LU (Chinese Medicine and Culture)
Abstract. Da Yuan Ben Cao (《大元本草》 Materia Medica of the Great Yuan Dynasty) is a materia medica book compiled during the Yuan dynasty. Because the book has not survived and the related Chinese historical resources are also very scarce, there have been always some controversies about whether the compilation of this book was ever completed or not. Based on a Chinese medical book named Ben Cao (《本草》 Materia Medica) which is mentioned in the preface of Tānksūqnāmah (《伊利汗中国科技珍宝书》 Ilkhanid Chinese Science and Technology Treasure Book), a Chinese medicine book in Persian, this article analyzes the compilation ways of Chinese scientific and technological books during the Ilkhanid dynasty and preliminarily points out that Da Yuan Ben Cao was introduced to Iran in the Yuan dynasty. Ben Cao in Tānksūqnāmah was very likely to be the Persian version of Da Yuan Ben Cao.